USING DC DECAY TESTS FOR DETERMINING THE MAGNETIZATION PARAMETERS OF THE AC ELECTRICAL MACHINES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The paper presents the use of a static experimental method (DC decay test) for determining the magnetization parameters of AC electrical machines. The magnetization characteristics, synchronous and differential magnetization inductances as functions of the total magnetizing current, were determined for two types of synchronous machines and an induction machine, respectively. The orthogonal d-q mathematical model in rotor coordinates was used, and the calculations were performed using MATLAB-Simulink. For the experimental tests, high-performance professional measuring devices were used.
Keywords: AC electrical machines; Magnetization parameters; DC decay test